2009
DOI: 10.1158/1078-0432.ccr-08-1360
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of an Oncolytic Adenoviral-CD40 Ligand (CD154) Transgene Construct in Human Breast Cancer Cells

Abstract: Purpose: CD40 ligand (CD40L, CD154) plays a central role in immunoregulation and also directly modulates epithelial cell growth and differentiation. We previously showed that the CD40 receptor is commonly expressed in primary breast cancer tissues. In this proof-of-principle study, we examined the breast cancer growth^regulatory activities of an oncolytic adenoviral construct carrying the CD40L transgene (AdEHCD40L). Experimental Design: In vitro and in vivo evaluations were carried out on AdEHCD40L to validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 46 publications
(56 reference statements)
3
35
0
Order By: Relevance
“…Therefore, it may be of relevance that it can be augmented by arming the virus with immune stimulatory molecules, such as CD40 ligand (CD40L). Preclinical studies have suggested that this approach can result in enhanced antitumor activity but human data has been lacking heretofore (11). Soluble CD40L (sCD40L) has been shown to mediate various antitumor activities in vitro and in vivo including direct growth inhibition and induction of apoptosis in different human tumor types (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it may be of relevance that it can be augmented by arming the virus with immune stimulatory molecules, such as CD40 ligand (CD40L). Preclinical studies have suggested that this approach can result in enhanced antitumor activity but human data has been lacking heretofore (11). Soluble CD40L (sCD40L) has been shown to mediate various antitumor activities in vitro and in vivo including direct growth inhibition and induction of apoptosis in different human tumor types (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have suggested that this approach can result in enhanced antitumor activity but human data has been lacking heretofore (11). Soluble CD40L (sCD40L) has been shown to mediate various antitumor activities in vitro and in vivo including direct growth inhibition and induction of apoptosis in different human tumor types (11)(12)(13). CD40L immunotherapy has also been shown to target the chemoresistant subpopulation of cancer cells (14) and has been suggested to sensitize chemoresistant tumors to cytotoxic drugs (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…CD40L transgene expression in human breast (9), ovarian (21), cervical (22) colon (26), bladder (27), non-small cell lung (28), skin (29), and squamous epithelial carcinoma cells (30) was found to produce a direct growth-inhibitory effect through apoptotic induction and/or cell cycle blockage with no overt side effects on their normal counterparts. The pro-apoptotic effects of CD40L are revealed upon disruption of the PI3 kinase/mTOR and ERK signaling pathways or inhibitor of de novo protein synthesis (13).…”
Section: Discussionmentioning
confidence: 99%
“…5-FU) or novel modalities (e.g. oncolytic viruses) also have displayed enhanced efficacy in pre-clinical animal models (9).…”
Section: Introductionmentioning
confidence: 99%
“…88 In another study, the gene encoding CD40 ligand was used due to its immunostimulatory activity. 89 Post et al made an oncolytic Ad armed with an interleukin-4 gene (HYPR-Ad-IL4). The interleukin-4 cytokine was chosen for its ability to induce a strong host antitumor immune response and for its potential antiangiogenic activity.…”
mentioning
confidence: 99%